Sistem Pendukung Keputusan dalam Penentuan Prioritas Pengembangan Kawasan Wisata Bawah Laut - Manda Rohandi; Moh. Yusuf Tuloli Mail; M. R. Thohir Jassin (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
The fact that Gorontalo Province lies between Sulawesi Sea and Tomini Bay has undoubtedly resulted in its having abundant underwater tourist spots. However, the insufficient availability of fund has led to poor management of those spots. Given the insufficient fund the government has, it is important to give priority to certain spots. This study aims to determine the developmental priority of underwater tourism spots in Gorontalo using Analitycal Hierarchy Process (AHP) and Simple Additive Weighted (SAW). These methods use five criteria and 28 alternatives in determining the best priority in development of underwater tourism spots in Gorontalo Province. The result of AHP and SAW calculation showed that the best spot should be prioritized to be developed is Pulo Cinta whose score is 0,9888. This decision making method will help government, who has the final say in the issue, give priority to the best spot to be developed.